THE RELATIONSHIP BETWEEN SMOKING HABITS AND THE INCIDENCE OF CHRONIC URTICARIA IN CIVITAS WIDYA MANDALA CATHOLIC UNIVERSITY SURABAYA - Harijati, Erna; Dian Putri, Maria Patricia; Tahalele, Paul L; Khoesasih, Antonius Kevin (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: Urticaria is a heterogeneous disease with multiple causative factors. A thorough literature research has revealed a very limited amount of evidence about the effects of smoking and alcohol consumption habits on the clinical characteristics of urticaria.. Atopic allergic which mean urticaria can affect all populations, but is most common in those aged between 20 to >60 years. Smoking has been reported to play a role in the onset of Urticaria. Substances in cigarette smoke can interact with body cells, resulting in the formation of free radicals or Reactive Oxygen Species (ROS).Objective: To see the relationship between smoking habit and the incidence of chronic urticaria among civitas at Widya Mandala Surabaya.Methods: The method used in this study was a case-control study by taking a population of civitas at the Widya Mandala Surabaya who had smoking history from 2020 to 2023. A sample of 94 people was obtained who had met the inclusion and exclusion criteria of the study. The sample of this study was divided into two groups consisting of a case group and a control group.Results: The results of the Contigency Coefficient Correlation test showed a significant p value of 0.031 <0.05, which means that there is an important correlation between smoking and the incidence of chronic urticaria among civitas at the Widya Mandala Surabaya.Conclusion: It is proven that there is a relationship between smoking and the incidence of chronic urticaria in civitas of Widya Mandala Surabaya.